Goellipora triasica n. gen. n. sp.: Eine sessile Foraminifere aus den norischen Dachstein-Riffkalken des Hohen Gölls (Nördliche Kalkalpen, Österreich) - Senowbari-Daryan, Baba; Zankl, Heinrich (Senckenbergiana Lethaea, 2000)
Foraminiferes are the most abundant and important epifaunal elements within the Norian Dachstein reef-complex of the Hoher Göll. Both, vagil-benthic and sessile groups, are represented. Among the sessile taxaAlpinophragmium, Calcitornella, Nubecularia, Planiinvoluta andTolypammina occur. In addition, a sessile, perforated and agglutinated (?) foraminifer was found, which is described here asGoellipora triasica n. gen. n. sp.
UnivIS-Import:2017-11-07:Pub.2000.nat.dgeo.IGM.LP.goelli
Keywords: Foraminifera; Upper Triassic (Norian); Dachsteinkalk; Hoher Göll; Austria